Analysis of endogenous hormones and transcriptomes involved in in vitro shoot apical dormancy during adventitious root formation in tree peony - Yang, Yujie; Gu, Yanan; Gao, Ping; Chen, Lan; Zhang, Qingxuan; Luo, Jie; Miao, Dapeng; Wen, Shusheng; Duan, Yu (Frontiers in Plant Science, 2025)
Tree peony (Paeonia sect. Moutan) is widely cultivated worldwide. However, conventional propagation methods such as sowing, division, and grafting are constrained by low reproduction rates and long reproductive cycles. Thus, micropropagation technology is a viable alternative to advance the tree peony industry. However, the industrial production of tree peony through this technique is largely limited by shoot apical dormancy in in vitro plantlets, and its molecular mechanism remains unclear. In this study, changes in endogenous hormone content during adventitious root formation were investigated in Paeonia × lemoinei ‘High Noon’. Transcriptome sequencing was carried out at four stages of root induction (0 d, 10 d, 20 d, 30 d) using Illumina HiSeq. The results showed that a decrease in trans-zeatin riboside (ZR) and gibberellic acid (GA3) content induced shoot apical dormancy. In contrast to previous studies, high levels of abscisic acid (ABA) were not the dominant factor inducing dormancy in in vitro tree peony plantlets. The accumulation of indole-3-acetic acid (IAA) in shoot apices promoted dormancy by activating the ABA signaling pathway without enhancing ABA levels. A total of 92.07 Gb of clean data were obtained, and 121,843 unigenes were assembled. The regulation of shoot apical dormancy is governed by core metabolic pathways, including plant hormone signal transduction, starch and sucrose metabolism, and phenylpropanoid biosynthesis. In these pathways, 27, 18, and 17 differentially expressed genes (DEGs) were identified, respectively. Based on the endogenous hormone content in the apical shoot and RNA-seq data collected during shoot apical dormancy, a preliminary model was constructed to illustrate how endogenous hormones regulate in vitro shoot apical dormancy in tree peony. These results provide rich gene resources for investigating the molecular mechanism underlying in vitro plantlet dormancy and will significantly contribute to advancing the tree peony industry by improving the transplant survival rate of micropropagation.